2005
DOI: 10.1111/j.1365-2966.2005.08755.x
|View full text |Cite
|
Sign up to set email alerts
|

A deep, narrow J-band search for protogalactic Ly  emission at redshifts z   9

Abstract: We present a deep, narrow J‐band search for protogalactic Lyα emission at redshifts z∼ 9. We combine an exceptionally deep image of the Hubble Deep Field South, obtained using a narrow‐band filter centred on the wavelength 1.187 μm using the VLT/ISAAC facility, with existing deep, broad‐band images covering optical to near‐infrared wavelengths. We search for z∼ 9 Lyα‐emitting galaxies displaying a significant narrow‐band excess relative to the Js band that are undetected at optical wavelengths. We detect no so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 41 publications
7
97
1
Order By: Relevance
“…The effects of the filter transmission curve on LAE detection and comoving volumes are detailed in e.g. Willis & Courbin (2005) and Hu et al (2010). Considering our null results, these effects will not affect our conclusions.…”
Section: Comoving Volumementioning
confidence: 93%
“…The effects of the filter transmission curve on LAE detection and comoving volumes are detailed in e.g. Willis & Courbin (2005) and Hu et al (2010). Considering our null results, these effects will not affect our conclusions.…”
Section: Comoving Volumementioning
confidence: 93%
“…The first observational constraint on the abundance of Ly emitters at z > 8 was presented by Willis & Courbin (2005). These authors conducted a narrowband imaging survey in the J band toward the Hubble Deep Field South and found no z = 8.8 sources with Ly luminosity greater than 10 42.5 ergs s À1 over a volume of approximately 990 Mpc À3 .…”
Section: Volume Density Of Z > 8 Ly Emittersmentioning
confidence: 99%
“…While narrowband surveys have had significant success at detecting Ly emitters at z ' 6 (Hu et al 1998(Hu et al , 2002(Hu et al , 2004Malhotra & Rhoads 2004;Hu et al 2005;Stern et al 2005; Kashikawa et al 2006;Shimasaku et al 2006), only one Ly emitter has been convincingly detected at z ' 7 . At z ' 9, narrowband surveys for relatively luminous Ly emitters (k10 42.5 ergs s À1 ) have yet to find any sources (Willis & Courbin 2005;Cuby et al 2007). While a few candidate Lyman break galaxies beyond z ' 7 have been suggested from photometric data (Bouwens et Henry et al 2007), none has yet been spectroscopically confirmed, largely as a result of the difficulties inherent to observing in the near-infrared.…”
Section: Introductionmentioning
confidence: 99%
“…Willis & Courbin (2005), Willis et al (2008) and Cuby et al (2007) have performed narrow-band surveys at z = 8.8 that yielded only upper limits of the Lyα LF of LAEs at this redshift. In this paper we present the results of a narrow-band imaging survey at z = 7.7 representing a factor of 10 improvement in area at approximately the same detection limit compared to our previous survey at z = 8.8.…”
Section: Introductionmentioning
confidence: 99%